BUILDING THE COMPETITIVENESS OF GEN ZPRENEURS THROUGH THE INTEGRATION OF A DIGITAL MINDSET, SOFT SKILLS, AND A COLLABORATIVE ECOSYSTEM - Novy Fitria (Management Study Program, Faculty of Economics, Merdeka University Pasuruan. East Java. Indonesia, 2026)
, Mahasaraswati